Rotor parameters of small weight helicopters - Dudnik, V.; Karabut, V.; Lesniak, S. (My University, 2020)
In recent years, a significant number of one and two-seats small weighted helicopters have appeared. This fact makes it possible to analyse the parameters and determine the parameter dependencies for this helicopters class. Knowledge of such dependencies is necessary for the preliminary design stage. The analysis performed in this paper and the comparison of it with the statistical data of all the categories of helicopters made it possible to determine the necessary corrections in the methods for design the parameters of the little helicopter's rotor systems.